Off-Grid Energy Technologies used in Rural Areas of India - Krishan Arora; Amardeep Singh Virdi (Bulletin of Electrical Engineering and Informatics, 2013)
Energy scenario in India is changing with a greater pace. Growth rate of villages has increased, likewise their energy demand. With the awareness of the decreasing natural resources, non conventional energy resources are gaining lots of interest in sparsely separated areas. The rural areas of India are having the huge scarcity of energy because of limited energy resources and Grid connectivity is not feasible due to economic factors and geographical situations. So we require to establish the off grid system for the benefit of the mass. Off-grid System’s commissioning and operation done as indigenous unit, and free from grid related problems like frequency and voltage regulations and they provides flexible operation because their emphasis is on extraction of energy and conversion into useful work. This paper discusses the potential use of off-grid energy technologies as an alternative for grid extension. Off-grid Energy systems provide the solutions to the basic energy needs in the rural areas of India. These indigenously build plants are not connected to any electrical utility and can be connected with the micro grid for the better reliable operation. Due to small size their demand and load management would be easy. Off-grid system utilizes the solar thermal radiation, wind energy, geothermal energy, tidal wave, Biomass etc. There is numerous numbers of applications where we can use this energy and decrease the dependence on conventional grid.